Economics of the law torts, contracts, property, litigation - Miceli Thomas J (New York OUP, 1997)
This book provides a few core areas of the law with an emphasis on methodology. Here also reflects a detailed analysis of the traditional common law topics of torts, contracts, and property, along with issues related with litigation-settlement decision.
Keywords: Law and economics